Combining Professional and Private Life in Poland: Searching for the Consensus Between Employers and Employees - Mariola MIROWSKA; Izabela ZIEBACZ (Communications of International Proceedings, 2021)
Since the beginning of the 90s the influence of globalization and the increasing economic competition caused a negative influence of work on family life. In effect this causes serious difficulties in reconciling work and family duties. The management tries to find solutions to make subordinates more involved in work. It’s not easy, especially in times of careful spending on long-term investments. The shortage of in-depth research is undoubtedly a fairly significant barrier to the implementation of work-life balance (WLB) programs. The lack of economic measures results in ignorance, focus on current organizational problems and lack of perspective thinking.  It cannot be denied that WLB issues will be a growing challenge for companies. On the one hand, the issues arise from the need to employ women, and on the other hand, it is often heard today that employees (women - mothers) abuse their sick leave. However, there is no cost-effective mechanism that would aid the employee to solve unexpected, private life problems, such as e.g. sudden child illness, illness of a babysitter etc. Without the institutionalized workplace support, the employees often inform their supervisors of the absence at work as a fait accompli. This situation usually creates problems for the employer. The purpose of this paper is the attempt to look at the issues of WLB in a systemic way. We present a concept of the management of WLB in real-life conditions through systemic response to random situations resulting from sudden and necessary care for children under the age of 8.
Keywords: Work-Life Balance; Social Development; Professional Feminization; Social Pedagogy.